A possible association of HLA‐C*07:18:01:01 and HLA‐B*58:01. (6th December 2018) - Yang, K. L.; Lin, P. Y.
Abstract : HLA‐C*07:18:01:01 is possibly in association on the same haplotype as HLA‐B*58:01 .